Damaging wind storms in North Eastern Argentina: seven case studies - Natalini, Bruno (2012)
Argentina is a large country with several areas dominated by different climate mechanisms. Since 2008, damage to civil structures caused by strong winds has been surveyed in Chaco and the neighbouring areas. Chaco is a province of NEA, the north-east region of the Argentina, which also includes the provinces of Formosa, Corrientes and Misiones. The strong wind events in NEA are related to severe convective storms. In this work, we present findings about wind-induced damage in NEA and the prevailing meteorological conditions. We emphasise seven particular cases for which the conditions of the atmosphere were reconstructed through reanalysis.